Antibacterial Activity of Copper Oxide (CuO) Nanoparticles Biosynthesized by Bacillus sp. FU4: Optimization of Experiment Design - Mojtaba Taran, Maryam Rad, Mehran Alavi (Tabriz University of Medical Sciences, 2017)
Background: There are several methods for synthesis of metallic nanoparticles (NPs) including chemical, physical and biological process. In this study, Bacillus sp. FU4 was used as biological source for biosynthesis of CuO NPs. Methods: CuO NPs have been prepared by copper sulfate (CuSO4). CuO NPs were formed after oxidation of Cu NPs. Design and analysis of Taguchi experiments (an orthogonal assay and analysis of variance (ANOVA)) carried out by the Qualitek-4 software. Average effect of CuSO4 concentration (0.1, 0.01 and 0.001 M), incubation and culturing time (48, 72, 96 hours) as three controllable factors with three levels were evaluated in CuO NPs biosynthesis. Characterization of CuO NPs was determined by UV-Vis spectroscopy, X-ray diffraction (XRD), Fourier transform infra-red (FT-IR) spectroscopy and scanning electron microscopy (SEM). Also, the antimicrobial properties of CuO NPs were investigated using Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 43300 as multidrug resistant (MDR) bacteria. Results: Results: It was evaluated that, NPs size distributions were in the range of 2-41 nm with spherical shapes. The anti-bacterial activities of CuO NPs were measured based on diameter of inhibition zone in disk diffusion tests of NPs dispersed in batch cultures. Two levels of CuSO4 concentrations (0.1 and 0.01M) had antibacterial effect on E.coli (33±0.57 and 6 ±2mm). In the case of S. aureus, there was surprisingly no sign of growth. Conclusion: CuO NPs have antibacterial activity that can be benefit in medicinal aspect for fighting against prominent pathogen bacteria such as E.coli ATCC 25922 and S.aureus ATCC 43300.